Evaluation of anti-hypertensive drug utilisation and cost in Hospital Tengku Ampuan Afzan, Kuantan - Mohd Shah, Azarisman Shah; Abdullah, Aszrin; Mohamed, Sahimi; Abdullah Ngow, Harris; Omar, Ahmad Marzuki; Ab Rahman, Jamalludin; Satwi, Sapari; Oteh, Maskon (Faculty of Medicine, International Islamic University Malaysia, 2009)
Introduction: Hypertension is one of the most important risk factors for cardiovascular disease in Malaysia. The prevalence of hypertension nearly doubled over a ten-year period (1986 – 1996). This has resulted in a significant rise in its attendant cost. We aim to review the institutional anti-hypertensive use, the cost incurred and the implications on management in our local setting. Materials and Methods: A retrospective review of the annual cost (2006) of anti-hypertensive medications was undertaken at the Department of Pharmacy, Hospital Tengku Ampuan Afzan, a 600-bed major regional hospital on the east-coast of Malaysia. The total number of prescriptions given out and the total cost per drug is then factored to give the annual cost per drug per person in a percentage of the total annual expenditure. Results: The majority of patients were on either 2 (46.5%) or 3 (25.9%) anti-hypertensives. The most frequently prescribed medications were ACE Inhibitors (33.45%), Calcium channel blockers (29.63%), diuretics (16.67%) and β-blockers (13.64%). In terms of cost however, the Calcium channel blockers constituted the greatest percentage of the annual anti-hypertensive budget (63.67%) compared to ACE Inhibitors at just 20.04% of the annual expenditure. The least costly group of drugs is the diuretic making up 16.67% of the total annual prescriptions but only constituting 1.23% of the annual cost. Conclusion: The majority of patients were on ACE Inhibitors and/or Calcium channel blockers. This has huge monetary implications as they represent a large proportion of the annual antihypertensive allocation. There may be a need to reverse the trend in the developing world due to cost restrictions.